1999
DOI: 10.2114/jpa.18.219
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heart Rate Variability during Mental Task with Reference to Ambient Temperature.

Abstract: Abstract. The purpose of this study was to evaluate the cardiac autonomic control over mental task under various ambient temperatures (21 C, 28 C and 35 C). Seven healthy male subjects engaged in the mental tasks, which consisted of distinctive reaction-time tasks. Respiratory coefficient of variation of instantaneous heart rate (CVRESP), derived from the cross-correlation function between heart rate and respiratory curve, was used as a parameter to assess parasympathetic nervous functions. The difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…, ambient temperatures and illumination levels were significantly different across the two conditions. In general, lower ambient temperatures have been shown to reduce the subjects’ HR [ 48 ] and increase their SBP and DBP [ 49 ]. However, previous studies have been conducted under even greater changes in ambient temperature, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ambient temperatures and illumination levels were significantly different across the two conditions. In general, lower ambient temperatures have been shown to reduce the subjects’ HR [ 48 ] and increase their SBP and DBP [ 49 ]. However, previous studies have been conducted under even greater changes in ambient temperature, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have been conducted under even greater changes in ambient temperature, i.e. , 21 °C vs. 28 °C [ 48 ] and 15 °C vs. 0.5 °C [ 49 ]. Moreover, in the aforementioned study, the 7 °C change from 15 °C–8 °C did not alter the subjects’ SBP and DBP values [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other authors described similar dynamics of the heart rate during mental load too see e.g. 2,3,4,5,11 . The increased activity of the sympathetic nervous system was probably the main cause of subjects' high heart rate when they solved the cognitive tasks.…”
Section: Discussionmentioning
confidence: 66%
“…Given that the stimuli in these factors are divided into passive and active inputs, environmental and mental factors deliver passive and active stimuli to the autonomic nerves, respectively. Through investigations on the combined effects of environmental and mental factors on cardiac autonomic responses (Ishibashi and Yasukouchi, 1999), it is suggested that parasympathetic activity might control the basal effect of ambient temperature and the other components, including sympathetic activity contributing to the increase in HR due to mental tasks. A notable result was that the mental task activated HR consistently via sympathetic control as active stimuli, while the parasympathetic activity was affected gradually with alterations of the ambient temperature as passive stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…However, they provided no information about the effect of mental tasks on HR under progressive autonomic alterations by passive stimuli. Previous study (Ishibashi and Yasukouchi, 1999) has shown the effect of mental task under gradual alteration of parasympathetic activity is portrayed as passive stimuli. In this study, therefore, we investigated the effect of mental tasks on autonomic control during physiological manoeuvre, such as passive graded head-up tilting, that increases sympathetic activities (Iwase et al, 1987;Mukai and Hayano, 1995).…”
Section: Introductionmentioning
confidence: 99%